SIMULATION-BASED TRAINING IN THE DEVELOPMENT OF CLINICAL THINKING AND SURGICAL SKILLS IN THE DIAGNOSIS AND TREATMENT OF ODONTOGENIC PHLEGMON IN STUDENTS OF THE DENTAL FACULTY FACULTY (International journal of medical sciences, 2026)
Odontoid phlegmons are severe purulent-inflammatory diseases of the maxillofacial region that require dental students to have well-developed clinical thinking and practical surgical skills. The aim of the study was to evaluate the effectiveness of simulation-based training using clinical scenarios and a biological model. A comparative analysis of knowledge, clinical thinking, and practical skills before and after training showed a statistically significant improvement in training, increased confidence in performing surgical procedures, and increased motivation to learn. The results of the study demonstrated a statistically significant improvement in the professional training of students, increased confidence in performing surgical procedures, and increased motivation to learn, confirming the high pedagogical effectiveness of the method.